Giuseppe Caglioti con Tatiana Tchouvileva e Luigi Cocchiarella, ODI et AMO. Dalle ambiguità percettive al pensiero quantistico, Mimesis, Milano 2020 (diségno, 2022)
It is not so unusual to leaf through a book before reading it, without even being sure to do it later. The accomplished act that summarizes this operation, traditionally considered an instinctive and common belief to many, is often depicted in the iconic paintings concerning the Annunciation of the Madonna. The Annunciation to the Virgin Mary is, in fact, one of the most represented themes in the history of art, and the three characters (Angel, Virgin, and the dove) involved in their meanings and signifiers, always interact within an architectural scene, in which the only accessory present is (almost always) a book. The pose of Our Lady towards this object is, in most cases, that of a pause or a rest, and here the doubt arises: if surprised by the event, she is interrupting the reading, or she is simply leafing through that book. [read more]